Biodisponibilidade de ferro e a anemia ferropriva na infância revisão sistemática - Lemos, Solange Bonandi (2012)
This article is a systematic review in which one employed national and international articles based on PubMed, SciELO and Bireme, whose main goal was to show the efficiency of iron-rich food and iron supplementation efficient usage by children. In selected field studies one could verify aspects positives for the participants’ health. From these participants had a recovery in their anemia condition and an increase in the concentration of hemoglobin. In 37,5% of the studies there was an improvement in the children’s performance, and in 75% there was a decrease in the anemia prevalence. Until the sixth month of life the breastfeeding totally supplies the iron need of children, after this period it is necessary to carry out a supplementation with iron-rich food in order to promote the children’s full development. Substituting the breastfeeding until the sixth month of life by cow milk or other food may endanger the child’s health